2006
DOI: 10.1177/0091270005284389
|View full text |Cite
|
Sign up to set email alerts
|

Use of Omeprazole as a CYP3A Probe Drug: Effect of Sex and Menstrual Cycle Phase on CYP3A Activity in Healthy Caucasian Adults

Abstract: To determine the effects of sex and menstrual cycle phase on CYP3A activity and to characterize the intraindividual variability of CYP3A, 24 Caucasian adults were given a single dose of omeprazole every 14th day for 3 months (men) or during the mid-follicular and mid-luteal phases over 3 full menstrual cycles (women). The 2-hour plasma metabolic ratio (MR) (omeprazole/omeprazole sulphone) was used as a measure of CYP3A activity. Overall mean MRs for men (2.4 +/- 1.2) and women (2.3 +/- 0.93) were not significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Interestingly, Zhang et al . () showed that higher endogenous progesterone concentrations in women could have a stimulatory effect on the P450 3A (CYP3A) activity, which plays an essential role in the metabolism of omeprazole in the liver (Andersson et al ., , ). However, all the females in the current study did not show signs of their first heat season until weeks after the last sample collection, and it has been shown that bitches have undetectable serum concentrations of progesterone during anestrous (Hase et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Zhang et al . () showed that higher endogenous progesterone concentrations in women could have a stimulatory effect on the P450 3A (CYP3A) activity, which plays an essential role in the metabolism of omeprazole in the liver (Andersson et al ., , ). However, all the females in the current study did not show signs of their first heat season until weeks after the last sample collection, and it has been shown that bitches have undetectable serum concentrations of progesterone during anestrous (Hase et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang and coworkers found a positive correlation between progesterone serum concentration and activity. 44) Taken together with the reports that CYP3A4 exhibits positive cooperative characteristics with substrates such as carbamazepine and 17β-estradiol in the presence of progesterone in an in vitro coincubation system, [36][37][38] they proposed the hypothesis that the increased activity observed in pregnant women is due to the enhancement of CYP3A4 activity by exposure to higher levels of progesterone. To date, it is unclear whether changes in the pharmacokinetics of CYP3A substrates during pregnancy are due to the induction of CYP3A genes, cooperative enhancement by steroids, or both, and further studies are required.…”
Section: Fluctuation Of Cyp3a Activity During Pregnancymentioning
confidence: 92%
“…(33-36) Changes in DME activities have also been described during periods of physiologic (37, 38) and pharmacologic (39, 40) hormonal fluctuation. At present, the impact of developmental alterations in sex and growth hormones on DMEs has not been similarly characterized.…”
Section: Growth and Sex Hormones As Biochemical Regulators Of Dmesmentioning
confidence: 99%
“…(Figure 6) This hypothesis is consistent with data which demonstrated a direct correlation between increased endogenous progesterone levels and CYP3A activity during the mid-luteal phase of the menstrual cycle. (37) Reduced activities of CYP2C19 and CYP1A2 are thought to be mediated by the high levels of estrogen that are present throughout gestation.…”
Section: Growth and Sex Hormones As Biochemical Regulators Of Dmesmentioning
confidence: 99%